2019
DOI: 10.2196/14292
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Using a Consumer-Based Mobile Meditation App to Improve Fatigue in Myeloproliferative Patients: Qualitative Study

Abstract: Background Myeloproliferative neoplasm (MPN) patients suffer from long-term symptoms and reduced quality of life. Mindfulness meditation is a complementary therapy shown to be beneficial for alleviating a range of cancer-related symptoms; however, in-person meditation interventions are difficult for cancer patients to attend. Meditation via a mobile phone app represents a novel approach in MPN patients for delivering meditation. Objective The study aimed to report MPN p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 43 publications
2
33
0
1
Order By: Relevance
“…In a study testing the same app as tested in this study, in cancer patients, data suggested significant decreases in self-reported fatigue. In open-ended interviews with those cancer patients reporting fatigue, 23% believed that improvements in their fatigue was a result of the meditation due possibly to sleeping better (less tired in daytime) or that the meditations allowed them a brief rest to recharge their energy levels [ 52 , 53 ]. Though the mechanisms of mindfulness meditation on sleep have not yet been determined, fatigue is a common complaint in those with sleep disturbance and should be investigated in future trials.…”
Section: Discussionmentioning
confidence: 99%
“…In a study testing the same app as tested in this study, in cancer patients, data suggested significant decreases in self-reported fatigue. In open-ended interviews with those cancer patients reporting fatigue, 23% believed that improvements in their fatigue was a result of the meditation due possibly to sleeping better (less tired in daytime) or that the meditations allowed them a brief rest to recharge their energy levels [ 52 , 53 ]. Though the mechanisms of mindfulness meditation on sleep have not yet been determined, fatigue is a common complaint in those with sleep disturbance and should be investigated in future trials.…”
Section: Discussionmentioning
confidence: 99%
“…En particular, para enfermería es fundamental integrar cuidados basados en las TCA (57) dado que aportan una dimensión que no se logra con la perspectiva biomédica. Lo anterior, implica utilizar las mejores evidencias, con diversos abordajes (58,59) que demuestren ser las intervenciones más efectivas para el cuidado de las personas con cáncer. En este sentido, es importante avanzar en estudios experimentales, que midan los bene cios de las TCA reportados por la investigación cualitativa (21,32) , tal como ya lo están haciendo centros integrales contra el cáncer en Sydney (60) y Corea (48) .…”
Section: Discussionunclassified
“…Also, recent systematic reviews and meta-analyses of app-based mindfulness interventions in the cancer population report high feasibility and acceptability; albeit engagement is an important variable to consider for intervention success [16,19,20]. However, while there are hundreds of commercially available mindfulness training apps, eg, Headspace, Calm, and 10% Happier [21,22], only Headspace has been customized for cancer patients and been scientifically evaluated [21]. Data from a randomized waitlist-controlled trial and a prospective cohort study of Headspace have demonstrated good overall efficacy for improving outcomes such as quality of life and anxiety in women diagnosed with breast cancer [21,23].…”
Section: Benefits Of App-based and Online Mindfulness Interventionsmentioning
confidence: 99%